SEROLOGICAL DETECTION OF BOVINE LEPTOSPIROSIS IN SUKABUMI AND CIANJUR REGIONS - Susanti, Susanti; Rachmawati, Faidah; Mulyadi, Andi; Sukatma, Sukatma; Purba, Hastuti Handayani S; Anastasia, Yessy; Ariyanti, Tati; Prihandani, Sri Suryatmiati (Jurnal Kedokteran Hewan, 2025)
This study aims to detect leptospirosis serologically and serovars found in cattle in the Sukabumi and Cianjur areas. 165 cattle serum samples were taken randomly in the Sukabumi and Cianjur region. Microscopic Agglutination Tests (MAT) were used for serological testing using the antigens of Leptospira serovar Icterohaemorrhagiae, Javanica, Celledoni, Canicola, Ballum, Pyrogenes, Cynopteri, Rachmati, Australis, Pomona, Grippotyphosa, Hardjo, Bataviae, and Tarassovi. The MAT results showed that positive serum leptospirosis in cattle in Sukabumi region was 18.75%, with serovars Hardjo 16.25%, Tarassovi 1.25%, and Hardjo and Tarassovi (1.25%). Meanwhile, in Cianjur region, positive serum was 30.60% with serovar Hardjo 22.35%, Tarassovi 2.35%, Icterohaemorrhagiae 1.18%, Grippotyphosa 1.18%, Hardjo and Tarassovi 1.18%, Cynopteri and Hardjo (1.18%), Rachmati, Pomona, Bataviae and Tarassovi (1.18%). Leptospira serovar Hardjo was the dominant serovar in both regions. Overall, one serovar was detected in 22.42% of cattle, two serovars in 1.82% and four serovars in 0.61% cattle.